The Impact of E-commerce on Traditional Retail Sales in Emerging Economies - Rajesh Kumar Sharma; Rahul Prakash Patel (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the effects of e-commerce growth on traditional retail businesses in emerging economies, focusing on market share shifts, consumer behavior, and sales trends. Analyzing data from Southeast Asian and African markets, the research reveals how e-commerce platforms are reshaping customer preferences, posing both challenges and opportunities for traditional retailers. Findings suggest that the rise of e-commerce is leading to a transformation of the retail landscape, with significant implications for future business models and strategies.